The Role of Health Workers in Handling People with Mental Disorders (ODGJ) Physical Restraint - Indriany Maya Ariusta; Sri Hernawati; Isa Ma’rufi (Humanistic Network for Science and Technology (HNST), 2018)
The problem of mental disorders in Indonesia is a significant health problem in this society because the disease of mental disorder in Indonesia is still quite high, based on the result of basic health research 2007 the prevalence of emotional mental disorder equal to 11,6% and varies between province and regency. The purpose of this study was to analyze the role of health workers covering preventive, promotive, education and evaluation in handling persons with mental disorders (ODGJ) physical restraint in Public Health Centers of Jember Regency. This type of research was a case study. Determination of informants using sampling technique purposive sampling. Number of informants were 9 people. The results of the research was that all informants have made promotive, preventive, education and evaluation efforts through counseling, screening, home visits and monitoring persons with ODGJ access in taking medication. Keywords: Role, Health workers, Mental disorders